How Did Students with Different Learning Profiles Experience ‘Normal’ and Online Teaching Situation during COVID-19 Spring? - Anna Parpala; Nina Katajavuori; Anne Haarala-Muhonen; Henna Asikainen (Social Sciences, 2021)
This study compares university students’ approaches to learning and experiences with the teaching–learning environment in general and during online studying as a result of the COVID-19 pandemic. It examines students’ learning profiles and how students with different learning profiles experienced the teaching–learning environment during COVID-19 as well as their approaches to learning and study-related burnout in general. The participants were 665 first- and second-year students. The profiles were examined using K-means cluster analyses and the differences in learning profiles using one-way ANOVA and the Tuckey Test. The results show changes in students’ approaches to learning and their experiences with the teaching–learning environment and study-related burnout within the different profiles when comparing a normal situation to the COVID-19 pandemic. We suggest that changes in study-related burnout can be different among different study profiles. The results imply that students with a fragmented knowledge base and difficulties in managing time and effort would require special attention in online teaching situations.